PHYSIOLOGICAL CHARACTERISTICS OF ASSOCIATED WITH SAPOTA LEAF SPOT NEOPESTALOTIOPSIS PROTEARUM (Journal of Plant Disease Sciences, 2025)
Characteristics leaf spot disease specimens were collected from a sapota orchard on the university campus and brought to the laboratory, where pathogens isolated using the hyphal tip method and pathogenicity was successfully demonstrated in pot cultures. Neopestalotiopsis protearum was identified as the isolate based on symptoms, cultural, morphological, pathogenicity testing, and molecular analysis. The current study was undertaken to explore the effect of temperature, relative humidity, light, effect and pH level on the growth development and sporulation of N. protearum, the cause of Sapota leaf spot. N. protearum exhibited maximum growth and sporulation at 30°C, with 25°C being the next best temperature. Both 20°C and 35°C exhibited similar impacts on mycelia growth, although 20°C produced more spores. The least growth was observed at 15°C and 40°C. The fungus thrived at 95 percent relative humidity, while 90% also supported good growth. A 12-hour light/dark cycle was ideal for growth, while continuous darkness also aided growth, however, continuous light impeded growth. The fungusfavored a pH of 7.0, but a pHof 6.5 also supporting good growth. Overall, the ideal conditions for N. protearum are 30°C, high humidity(>85%), a 12-hour light/dark cycle, anda pHof 7.0.
Keywords: Leaf spot; Neopestalotiopsis protearum; Physiological studies; Sapota